Variability of Weddell Sea ionospheric anomaly as deduced from observations at the Akademik Vernadsky station - Zalizovski, A.; Stanislawska, I.; Lisachenko, V.; Charkina, O. (Ukrainian Antarctic Journal, 2021)
Ionospheric Weddell Sea anomaly is an inversion of diurnal variation of the electron density in the ionosphere over Antarctic Peninsula, Weddell Sea, and neighbor territories observed during Antarctic summer. This paper aims at analyzing the reaction of the ionosphere during the Weddell Sea anomaly to changes in solar and geomagnetic activity as deduced from the data of vertical sounding of the ionosphere conducted at the Akademik Vernadsky station. The aim is achieved by comparing the monthly median values of the critical frequencies of the ionosphere (foF2) during Weddell Sea anomaly for the years of high and low solar activity; as well as by comparison of median December height-time diagrams (HT-diagrams) of foF2 calculated separately for the time intervals characterized by low or high levels of F10.7 and K indices for the period from 2007 till 2016. It was experimentally demonstrated that the Weddell Sea anomaly depends on the levels of solar ultraviolet flux and local K indices. The biggest nighttime maximum of ionization corresponds to low K indices and high values of F10.7. The most accurate inversion of diurnal variation of electron density in the F region is observed under the low values of K index and low F10.7 flux. The growth of geomagnetic activity decreases the nighttime ionization under both low and high levels of F10.7 fluxes and leads to a blur of the night maximum. Visible virtual heights of maximums increase together with F10.7 independently of the K index level. Blurring of the night maximum can be explained by destruction of the field of thermospheric winds supporting the nighttime anomaly, and/or by increasing role of plasma drifts in comparison with wind impact. The growth of visible virtual height of the nighttime maximum with increasing solar F10.7 flux could be explained by the gain of equatorward thermospheric wind with increasing solar ultraviolet flux that leads to growth of plasma upwelling effect. The Doppler frequency shift of the signals reflected from the ionosphere during nighttime in presence of the Weddell Sea anomaly is close to zero which could be explained by a stable F2 layer formed as a result of dynamic equilibrium between photochemical processes and upward plasma transport.